2013
DOI: 10.1016/j.pan.2012.12.121
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 regulates pancreatic stellate cell activity via the EP4 receptor

Abstract: Objectives-Pancreatic stellate cells are source of dense fibrotic stroma, a constant pathological feature of chronic pancreatitis (CP) and pancreatic adenocarcinoma (PDAC). We observed correlation between levels of cyclooxygenase-2 (COX-2) and its product prostaglandin E2 (PGE 2 ) and the extent of pancreatic fibrosis. Aim of this study was to delineate the effects of PGE 2 on immortalized human pancreatic stellate cells (HPSC) and to identify the receptor involved. The authors have no any potential conflict o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It has been shown that PGE 2 can downregulate tumor immunity through inhibiting dendritic cell (DC) differentiation and switching the function of DCs from induction of immunity to T-cell tolerance (Chinen et al, 2011); inhibiting CD8 1 T-cell proliferation and activity (Ganapathy et al, 2000); the inhibition of mature B-cell proliferation and induction of immature B-cell apoptosis (Shimozato and Kincade, 1999); downregulation of antitumor TH1 cytokines and upregulation of immunosuppressive TH2 cytokines (Fabricius et al, 2010); and inducing myeloid-derived suppressor cell differentiation (Sinha et al, 2007). More importantly, PGE 2 can bind to the EP2/4 receptor and activate the downstream cascades, leading to epithelium stem cell transition, metastasis, antiapoptosis, and proliferation (Rao et al, 2007;Rasmuson et al, 2012;Charo et al, 2013). PGE 2 induces the proliferation of colon and lung cancer cells by activating Ras-ERK and glycogen Fig.…”
Section: The Action Of Mrp4 In Pathophysiological Processesmentioning
confidence: 99%
“…It has been shown that PGE 2 can downregulate tumor immunity through inhibiting dendritic cell (DC) differentiation and switching the function of DCs from induction of immunity to T-cell tolerance (Chinen et al, 2011); inhibiting CD8 1 T-cell proliferation and activity (Ganapathy et al, 2000); the inhibition of mature B-cell proliferation and induction of immature B-cell apoptosis (Shimozato and Kincade, 1999); downregulation of antitumor TH1 cytokines and upregulation of immunosuppressive TH2 cytokines (Fabricius et al, 2010); and inducing myeloid-derived suppressor cell differentiation (Sinha et al, 2007). More importantly, PGE 2 can bind to the EP2/4 receptor and activate the downstream cascades, leading to epithelium stem cell transition, metastasis, antiapoptosis, and proliferation (Rao et al, 2007;Rasmuson et al, 2012;Charo et al, 2013). PGE 2 induces the proliferation of colon and lung cancer cells by activating Ras-ERK and glycogen Fig.…”
Section: The Action Of Mrp4 In Pathophysiological Processesmentioning
confidence: 99%